Dreadful acts / 2. - Ardagh, Philip (Ardagh, Philip. The Eddie Dickens trilogy ;, 2004)
Twelve-year-old Eddie Dickens survives encounters with an escape artist in a runaway hearse's coffin, a hot air balloon bearing the escape artist's lovely assistant, a gas explosion, and a jewel thief on the run.